KAJI EKSPERIMENTAL DAN NUMERIK TENTAN G FAKTOR KETANGGUHAN RETAK MODUS I DAN II PADA LAMINATE KARBON/EPOXY SERAT TERANYAM - Puja, IGN Wiratmaja; Suratman, Rochim; Ramelan, Aditianto; Prasetia, Hariadi Tri (Mesin, 2000)
This paper presents experimental and numerical analysis on the inï¬uence of crack orientations to the fracture toughness of mode I and mode II for woven type carbon/epoxy four ply laminate. The experimental procedure is carried out through off axis tensile test (ASTM D 3039-76) with nine variation of crack orientations i.e. 5Â°, 10Â°, 15Â°, 30Â°, 45Â° 65Â°, 75Â°, 80Â°, and 90Â°. Three rail shear test (ASTM D 4255-83) is utilized for zero degree crack orientation. The stress and strain contours around crack tips are obtained numerically using the ï¬nite element method. Numerical and experimental results of the mode I (KI) and mode II (KII) fracture thoughness are presented in graphical form as a function of crack directions. Adopting Wuâs(11) Criteria for unidirectional lamina and Hahnâs[6] Criteria for general anisotropic lamina, a new mixed mode fracture toughness criteria is developed for woven ï¬ber matrix laminate.